1929
DOI: 10.1002/ajpa.1330130126
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in mydriatic action of cocaine, euphthalmine, and ephedrine

Abstract: ONE FIGUREIn our investigation of the pupil-dilating effect of the natural or Z-ephedrine in subjects of different races, it was noted that the Chinese and negroes did not respond as well as Caucasians. This led to the examination of other mydriatics and the compilation of the present data to bring out actual racial differences as shown by the mydriatic action of cocaine, euphthalmine, I-ephedrine, dI-ephedrine, and d-pseudoephedrine.The observation period was one hour, because it was found that each drug reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
3

Year Published

1962
1962
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 0 publications
0
20
1
3
Order By: Relevance
“…While it is possible that presently unidentified factors may be contributory we believe the data support a racial difference in AAG concentration. Although racial differences in the mydriatic response to cocaine and ephedrine were noted over 60 years ago (Chen & Poth, 1929) differences in sensitivity to alcohol (Wolff, 1972) and more recently to propranolol (Zhou et al, 1989) have also been shown. It is important that in future such studies and kinetic studies in general evaluate the possible contribution of differences in drug binding when considering inter-ethnic differences.…”
Section: Resultsmentioning
confidence: 99%
“…While it is possible that presently unidentified factors may be contributory we believe the data support a racial difference in AAG concentration. Although racial differences in the mydriatic response to cocaine and ephedrine were noted over 60 years ago (Chen & Poth, 1929) differences in sensitivity to alcohol (Wolff, 1972) and more recently to propranolol (Zhou et al, 1989) have also been shown. It is important that in future such studies and kinetic studies in general evaluate the possible contribution of differences in drug binding when considering inter-ethnic differences.…”
Section: Resultsmentioning
confidence: 99%
“…A cútis do negro apresenta menor susceptibilidade ao efeito de substâncias irritantes ou alergia ao lá-tex, comuns nas dermatites de contato do pessoal paramédi-co 23,24 . O excesso de melanina na íris na musculatura radial e circular dificulta a ação de drogas midriátricas, como as antimuscarínicas (atropina) e α-adrenérgicas (fenilefrina e efedrina) 25,26 . O excesso de pigmentação da íris afeta o sistema trabecular e dificulta a drenagem do humor aquoso, determinando maior incidência de glaucoma (1:8) em relação ao branco (1:50).…”
Section: Sistemas Orgânicos Patologias E Ato Anestésicounclassified
“…Excessive melanin in the iris, radial and circular muscles impairs the action of mydriatric drugs such as antimuscarinic (atropine) and α-adrenergic (fenylephrine and ephedrine) drugs 25,26 . Excessive iris pigmentation affects the trabecular system and impairs aqueous humor drainage leading to a higher incidence of glaucoma (1:8) as compared to whites (1:50).…”
Section: More Peculiar Diseases To the Black Populationmentioning
confidence: 99%
“…For many years it has been recognised that racial factors may influence responsiveness to drugs, such as impaired mydriasis following standard doses of ephedrine and cocaine (Chen & Poth, 1929) and an insensitivity to atropine in Africans (Scott, 1945).…”
Section: Introductionmentioning
confidence: 99%